Effects of carob rich-polyphenols on oxidative stress markers and physical performance in taekwondo athletes - Gaamouri, Nawel; Zouhal, Hassane; Suzuki, Katsuhiko; Hammami, Mehrez; Ghaith, Aloui; El Mouhab, El Hafedh; C. Hackney, Anthony; Laher, Ismail; Ben Ounis, Omar (Biology of Sport, 2024)
Excessive exercise can induce cell damage and impair muscle function by generating oxidative stress. Carob rich phenolic components have attracted the attention of many researchers because of their antioxidant actions. We utilized a double-blind randomized placebo-controlled design to study the putative antioxidant role of six weeks of daily polyphenol supplementation on selected blood markers of oxidative stress and performance in taekwondo athletes. We studied the effects of daily supplementation with carob (40 g/d, for six-weeks) on performance levels and antioxidant capacity in 22 taekwondo athletes (age 21.9 ± 1.2 years; height 1.66 ± 0.34 m; weight 68.3 ± 16.9 kg; women = 10, men = 12) using a randomized, double-blinded study. Participants were divided into an experimental group (EG) or placebo group (PG). All athletes performed a frequency speed of kick test mult (FSKT mult ) before and after a six-week training period. Superoxide dismutase (SOD), catalase (CAT), and malondialdehyde (MDA) were measured 5 min after a FSKT mult . Physical performances improved significantly after six weeks in EG compared to PG for kicks number per set (from set 1 to set 5: p = 0.032, d = 0.70; p = 0.020, d = 0.77; p = 0.001, d = 1.12; p = 0.001, d = 1.25; p = 0.003, d = 1.01), total kicks number (p = 0,002, d = 1.04), and kick decrement index (%) (p = 0.017, d = 0.13). There were significant increases in CAT (p = 0.001, d = 1.85) and SOD (p = 0.001, d = 1.98) activities and significant decreases in MDA levels (p = 0.002, d = 0.81) in the EG. Carob supplementation during a six-week training program reduced oxidative stress and improved physical performance levels in taekwondo athletes.